2021
DOI: 10.1186/s12889-021-11266-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in 5-year weight change between younger and older US firefighters

Abstract: Background Research consistently finds that, on average, firefighters gain weight over time and some data indicate that younger firefighters are more likely to gain weight than older firefighters. The purpose of this study was to estimate the 5-year weight change among younger and older US firefighters. Methods Data from two occupational medical exams separated by 5 years (2009–2016) were examined from a cohort of US career firefighters in Virginia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Employing jumping jacks in PT, or even as a disciplinary method outside of PT, is important for maintaining recruits' lean body mass and their resistance to heat stress in hot environments. A previous study [30] revealed that young re ghters were more likely to gain weight and less likely to lose weight compared to older re ghters. As for the optimal number of jumping jacks, recent recommendations [31] have identi ed a regimen of 50 to 100 jumping jacks performed 3 to 5 days per week in sets of 10 as bene cial, particularly for bone density, which supports the experts' intensity categorisation in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Employing jumping jacks in PT, or even as a disciplinary method outside of PT, is important for maintaining recruits' lean body mass and their resistance to heat stress in hot environments. A previous study [30] revealed that young re ghters were more likely to gain weight and less likely to lose weight compared to older re ghters. As for the optimal number of jumping jacks, recent recommendations [31] have identi ed a regimen of 50 to 100 jumping jacks performed 3 to 5 days per week in sets of 10 as bene cial, particularly for bone density, which supports the experts' intensity categorisation in this study.…”
Section: Discussionmentioning
confidence: 92%
“…The variations in body fat percentage observed between our findings and those of other studies may be due to the characteristics of the sample being studied, such as participation in different wellness programs [28], differences in rank [29], etc., or variations in the assessment methods [28]. A recent study conducted over a five-year period in the United States, which investigated weight changes among firefighters aged below 45 years and those aged 45 years and above, revealed obesity rates of 25% among the younger group and 35% among the older group [30]. Notably, younger firefighters experienced a significantly higher weight gain compared to their older counterparts [30].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted over a five-year period in the United States, which investigated weight changes among firefighters aged below 45 years and those aged 45 years and above, revealed obesity rates of 25% among the younger group and 35% among the older group [30]. Notably, younger firefighters experienced a significantly higher weight gain compared to their older counterparts [30]. Moreover, a meta-analysis demonstrated that the prevalence rates of overweight and obesity within the firefighter population were 44.1% and 35.6%, respectively [31].…”
Section: Discussionmentioning
confidence: 99%